TRACKING PANCASILA STUDENTS : BUILDING THE NEXT GENERATION BASED ON NATIONAL VALUES - Aisyah Nurul Haq; Effendi Nawawi (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2024)
This article utilizes a library research method to explore the role of Pancasila students in strengthening national identity and values in Indonesia. By analyzing relevant literature, the article delves into the contributions of Pancasila students in applying Pancasila values in daily life and their impact on shaping the character of future generations. Through a critical approach to theoretical sources and empirical research, this article identifies the challenges and opportunities in implementing Pancasila student programs. Furthermore, it offers policy recommendations based on the findings from the reviewed literature. The analysis reveals that Pancasila-based character education is crucial for cultivating a young generation with a strong awareness of moral values and commitment to nation-building. Thus, this article provides insights into how the role of Pancasila students can be strengthened through a library research approach and underscores the importance of character education in advancing Indonesia as a sovereign and dignified nation